Penyuluhan Dan Instalasi Kelistrikan Pada Mesin Pemisah Kulit Ari Kedelai UMKM Produksi Tempe Tradisional Di Desa Wringinpitu Banyuwangi - Putra, Adi Pratama (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
Problems found in related to electrical installations in buildings/houses are not arranged perfectly or the installation is not following to the procedure because there have been improvements to the electrical installations of the building or house beforehand. Electrical installations that will be installed should also consider the concept of savings and costs Installation and addition of electrical installations with equipment that is not based on knowledge of electrical installations can be dangerous if not carried out by save maintenance and security of existing electrical equipment. Based on the situation analysis of MSME traditional tempe producers that have a separator machine using an electric motor, there is a need for a good and correct electrical installation to prevent the user avoid from electrical shock that could be potentially dangerous, because the separator from the soybean skin is a direct contact with water. The method of implementation in community service activities at Tempe producers MSMEs include; Field Observation, Tool Design, Tool Assembly, Tool Testing, Tool Installation, Electricity Installation, Electricity and Operation Training, and MONEV. The results of a series of community service activities that have been carried out are being able to increase the knowledge of all who are on the business purposes to understand how electricity and good installation are save from an unwanted thing about electricity.